Commentary on the book Exiliados, expatriados e integrados: chilenos en Costa Rica (1973-2018), by Mario Oliva Medina (coordinator) - Rebolledo González, Loreto (2022)
A comment is made on this book, coordinated by Mario Oliva and published by the National University Editorial in 2021, which is the result of an exhaustive and rigorous investigation supported by a variety of written and oral sources. Four chapters address the solidarity received by the Chileans who arrived in Costa Rica after the coup, considering the political and sociocultural dimensions of their integration, the insertion of academics in various universities; the meanings that exiles assign to the exile experience based on their subjectivities and a look at the exile of the painter Julio Escámez Carrasco. It is remarkable and novel that the text is located in the host country, with its center in the Chilean exiles but in a permanent dialogue with the context of the country to which they arrived and were integrated, showing how their presence had repercussions in various spheres of Costa Rican society generating mutual benefits.